(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
Endospermum malaccense or locally known as Sesendok is one of the timber species belong to the family of Euphorbiaceae. It has a good characteristic in term of growth performance and wood properties similar with rubberwood. From the previous research, it has the potential to be a timber replacement to the rubberwood since the resource of rubberwood is decreasing. Therefore, the conservation of the superior genotype of Sesendok is necessary to take place in order to preserve the gene source of superior genotype. The process to conduct the ex-situ conservation must follow the scientific procedure to ensure the material taken can survive in the new environment. The selection of the Sesendok was conducted at three different populations. The selection of superior mother trees was based on the phenotypic and also wood properties. The establishment of ex-situ conservation (germplasm) for Sesendok will ensure the gene bank material resources keep well conserve. The result of survival rate for the wilding varies from 5% to 30% based on the height and size of the wilding. While for the seeds collected, germination rate varies from 80-95%. Ex-situ conservation and planting of Sesendok in large scale would be the answer to preserve the selected genotype for future breeding program and ensure sustainable supply of raw material to the industries.